Ginsenoside Drug Nanocomposites Prepared by the Aerosol Solvent Extraction System for Enhancing Drug Solubility and Stability - Tao, Cheng (Pharmaceutics, 2018)
Ginsenosides are the pharmacologically active constituents of ginseng. So far, more than 30 ginsenosides have been identified and widely used in pharmaceutical formulations. However, the therapeutic applications of ginsenosides are hampered by their poor solubility and low bioavailability. In this study, we selected two of the most important ginsenosides-Re and Rh(2) as model drugs to prepare ginsenoside drug nanocomposites (NanoGS) using the simple aerosol solvent extraction system (ASES) technique to address the poor solubility and bioavailability of these compounds. Compared with raw ginsenosides, NanoGS exhibited significantly enhanced dissolution rate owing to their low crystallinity and high surface area. Furthermore, in vitro cellular investigations showed that NanoGS-Rh(2) exhibited outstanding anticancer activity against MCF-7 cancer cells. Therefore, this study is expected to provide a promising strategy that could optimize and broaden the applications of ginsenosides, as well as other water-insoluble drugs in pharmaceutical formulations.